THE ENCOUNTER OF DA’WAH DIGITALIZATION WITH URBAN MUSLIM CULTURE - Dawam Multazamy Rohmatulloh; Mochammad Irfan Achfandhy; Astuti Patmaningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2023)
This research aimed to explore the encounter of da'wah digitalization with urban Muslim culture. The attention on this topic was due to the concern about the dislocation of traditional da'wah activities because of the demands of a fluctuating, fast-paced, and dynamic urban culture associated with the transformation from conventional to digital media. A virtual ethnography approach was applied with the data collected through Google Trends and analyzed manually. The results showed that da'wah media, such as images, videos, memes, animations, and podcasts, was becoming a significant trend among netizens. The media was associated with speed, effectiveness, as well as time and cost efficiency in delivering da'wah messages, which was particularly relevant for urban Muslim with fast-paced and hectic lifestyles. Da'wah digitalization also reinforced the urban Muslim culture of instant religious fulfillment. However, the tendency to consume da'wah materials instantly was associated with the risk of disseminating inaccurate religious information and disrupting the fragmentation of religious authority. This showed the need for careful monitoring and management of digital da'wah content to ensure the quality and sustainability of balanced religious education in a dynamic urban context.